Firing properties of motor units during fatigue in subjects after stroke - Hu, X.L.; Tong, K.Y.; Hung, L.K. (Journal of electromyography and kinesiology, 2006)
The purpose of this work was to investigate the electromyographic (EMG) fatigue representations in muscles of subjects after stroke at the level of motor unit, based on the analysis of mean power frequency (MPF) in the power density spectrum (PDS) for intramuscular EMG and our previous modeling and experiment studies on the neuromuscular transmission failure (NTF). NTF due to the local muscular fatigue had been captured in motor unit signals from healthy subjects during a submaximal fatigue contraction previously. In this study, the EMG signals for the biceps brachii muscles were collected by needle electrodes from the affected and unaffected arms of six hemiplegic subjects after stroke, and from the dominated arm of six healthy subjects during a full maximum voluntary contraction (MVC) and a subsequent 20% MVC. The MPF of EMG trials detected intramuscularly during the full and 20% MVCs, and the parameters of motor unit action potential trains (MUAPTs) during 20% MVC were analyzed in three groups: the normal (from healthy subjects), unaffected (from subjects after stroke), and affected (from subjects after stroke). It was found that during the full MVC the MPFs of the normal and unaffected groups decreased more than the affected when monitored by a moving time window of 2 s. The comparison on the overall MPF during the full MVC for these three groups over the whole time course of the EMG signal (18 s) were: the affected overall MPF was higher than the unaffected ( P < 0.05); and the unaffected overall MPF was larger than the normal ( P < 0.05). However, no significant decrease in MPF was found for these three groups during 20% MVC. The NTF was captured in most MUAPTs in the groups of the normal and unaffected rather than in the affected group, symbolized by the lowered rates of change (RCs) of firing rate (FR) ( P < 0.05), more MUAPTs with positive RCs of maximum oscillation (MO) in MUAPT power density spectra ( P < 0.05), and the significant higher RCs of minimum inter-pulse interval (MINI) ( P < 0.05) in the normal and unaffected compared to the affected group. Enhanced neural drives to the motor units of the unaffected and affected groups were observed during 20% MVC, which possibly came from the bilateral neural inputs due to the disinhibition of the ipsilateral projections in subjects after stroke. For identifying the fatigue associated with NTF, the motor unit firing parameters, FR, MINI, and MO, were more sensitive than the MPF. The results obtained in this work provided a further understanding on the EMG of the fatigue processes in paretic and non-paretic muscles during voluntary contractions.